The quality and technological parameters of milk obtained from dairy cows with subclinical mastitis - Magdalena Zalewska; Paulina Brzozowska; Magdalena Rzewuska; Ewelina Kawecka-Grochocka; Daria M. Urbańska; Tomasz Sakowski; Emilia Bagnicka (Journal of Dairy Science)
ABSTRACT: Mastitis is one of the most common diseases in dairy cattle. It significantly reduces milk quality and yield, thus incurring economic losses for farmers. This study investigates the impact of various bacterial pathogens on the SCC, milk composition, and technological properties of milk samples from 302 clinically healthy Polish Holstein-Friesian cows kept under intensive rearing conditions. Of the 462 milk samples analyzed, 85.06% were contaminated with bacteria. The majority were coagulase-negative staphylococci (52.60%). Escherichia coli, Streptococcus dysgalactiae, and Streptococcus uberis, (Group 4) and Staphylococcus aureus and Streptococcus agalactiae (Group 5), collectively considered major pathogens, were identified in 16.66% of samples; their presence was associated with higher SCC levels. Additionally, contamination with Staph. aureus or Strep. agalactiae had prolonged clotting time, adversely affected curd and whey quality, with curd yield remaining unaltered. Bacterial contamination did not appear to significantly affect the yield of milk or its main components, namely protein, casein, lactose, fat, TS, solid nonfat, free fatty acid, or citric acid. Although pH, freezing point depression (FPD), and acidity also remained unaffected by bacterial contamination, they were significantly influenced by herd-year-season of calving and herd-year-time of sampling interaction effects. The results indicate that the presence of bacteria causing subclinical mastitis negatively influences milk processing potential. However, fixed linear regression indicated that the number of colony-forming units (cfu/mL) only had a significant influence on FPD and clotting time, and as such, the number of bacteria in a sample did not influence milk yield or quality during subclinical chronic mastitis.